Single fasting plasma glucose measurement compared with 75 g oral glucose-tolerance test in prediction of adverse perinatal outcomes: a prospective cohort study from China. (October 2016) - Shen, Songying; Lu, Jinhua; Zhang, Lifang; He, Jianrong; Li, Weidong; Chen, Niannian; Wen, Xingxuan; Xiao, Wanqing; Yuan, Mingyang; Qiu, Lan; Cheng, Kar Keung; Xia, Huimin; et al.
Abstract: Background: The prevalence of gestational diabetes mellitus has increased markedly in recent years in China, mainly because of the introduction of new diagnostic criteria. We aimed to evaluate whether in the diagnosis of gestational diabetes mellitus, 1h and 2h glucose measurements have additional value compared with a single fasting plasma glucose measurement. Methods: We included data from 6993 pregnant women who underwent a 2h 75g oral glucose-tolerance test at 22–28 weeks' gestation in the Born in Guangzhou Cohort Study in China. Outcomes included having a large for gestational age baby (≥90th percentile), caesarean section, spontaneous preterm birth, and pre-eclampsia. We calculated the area under the receiver operator characteristic curves (AUC) to assess the capacity of oral glucose-tolerance test values to predict outcomes. Findings: The prevalence of large for gestational age babies was 10·8% (695 of 6448). The AUC for prediction of large for gestational age was greater for fasting plasma glucose than for 1h (0·604 vs 0·556, p=0·0002) and 2h glucose tests (0·604 vs 0·552, p<0·0001). Addition of 1h or 2h glucose values, or both, to the predictive model did not increase the AUC for fasting glucose (0·605 for addition of 1h and 2h values, p=0·564). Compared with women who had a fasting plasma glucose concentration lower than the 90th percentile, women with fasting plasma glucose equal or greater than the 90th percentile had a greater risk of having a large for gestational age baby (20·1% [129 of 641] vs 9·7% [566 of 5807], adjusted odds ratio 2·04, 95% CI 1·62–2·56), and post-load glucose concentrations had limited effect on that probability. Similarly, post-load glucose concentrations contributed little to the prediction of preeclampsia, spontaneous preterm birth, and caesarean section. Interpretation: In the diagnosis of gestational diabetes mellitus in a Chinese population, a single fasting plasma glucose measurement can predict whether women are at increased risk of having a large for gestational age baby. Funding: Guangzhou Science and Technology Bureau, Guangzhou, China